Lumbago en el embarazo - Urturbia M., Viviana (Revista Hospital Clínico Universidad de Chile, 2018)
Low back pain is one of the most frequent causes of pain during pregnancy and often gets worse as it progresses. This pain can interrupt daily activities, work and has a great impact on the quality of life of the pregnant woman. Its etiology is unknown and there are several theories that would explain that the genesis of pain is multifactorial. As the pregnancy progresses, there are several physiological changes that occur in the woman’s body, which could contribute to triggering a low back pain. It has been shown that an adequate diagnosis and early management based mainly on education, exercise and physiotherapy, achieve good results in the control of pain and improve the quality of life. In certain cases, the use of drugs for a limited period of time and with medical supervision may be beneficial in controlling pain.